INTEGRATING CIRCULAR ECONOMY PRINCIPLES INTO OPERATIONAL STRATEGIES - Anwar, Hairul; Kadafi, Muhammad Amin; Judiarni, Justina Ade; ZA, Saida Zainurossalamia (Penelitian dan Pengembangan Ilmu, 2024)
Circular economy principles are increasingly important in supporting the sustainability of company operations, but their application in operational strategies is still less systematically mapped out. This research aims to identify the circular economy principles that are most often integrated into operational strategies through approaches Systematic Literature Review PRISMA protocol based. The research results revealed four main principles, namely Reduce, Reuse, Recycle, Closed-loop Production Systems, Prolonging Product Life Cycle, And Resource Efficiency and Waste Minimization, which contributes significantly to the company's operational efficiency and sustainability. This study provides new insights to the academic literature and practical guidance for industry in adopting the circular economy.